Implementasi Sema Nomor 3 Tahun 2023 di Pengadilan Agama Samarinda (Studi Terhadap Persepsi Para Pihak) - Mulyadi; Lilik Andaryuni (CV. Creative Tugu Pena, 2024)
The state, through the Supreme Court, is trying to reduce the divorce rate by strengthening the principle of making divorce difficult through Supreme Court Circular Letter (SEMA) Number 1 of 2022 and then changing it to SEMA Number 3 of 2023. This circular letter stipulates that divorce must have been separated for six months. forever. However, this circular letter gave rise to a new polemic because it conflicted with the existing Sighat Taklik. Sighat Taklik provides a condition of three months without providing mandatory maintenance so that a wife can sue her husband for divorce. Facts on the ground also show that not all judges implemented the circular. The author found that there was a divorce case at the Samarinda Religious Court where they had not been separated for 6 months but the judge granted their divorce request. There are other cases where the judge's application for divorce was rejected because they had not been separated for 6 months. This has become a new polemic among society. This is also in line with the opinion of the Supreme Court which states that the Supreme Court Circular Letter is a form of circular from the Supreme Court to all levels of the judiciary which contains guidance in the administration of administrative justice.